Video Assignment: Integration of technology embrace learning in media news reporting - Nik Muhamad Zulkeffli, Nik Nurain Aliaa; Ramli, Muhammad Nurazizi; Abdul Halim, Muhammad Azib Zikry; Mohd Azni, Zuliani; Abd Aziz, Siti Hajar (2020)
Compare to conventional learning chalk and talk in classroom, it is adequately to expose thestudents with comprehensive and innovative learning tool. Although students guided by thelecturer during the class, extra, through video assignment students perceived greater creativity in conducting their own research about news reporting. This study aims to understand the roleof technology embrace learning in media news reporting through video assignments. In-depthinterview was done and recorded digitally with Ryan Chua, Programme Coordinator at Pusat Komunikasi Masyarakat (KOMAS) with regards to the issue related to newspaper coverageand its role in maintaining racial harmony in Malaysia. Students adopting video recording andediting as a versatile learning tool. Further, results demonstrated that students were clearlypreferred to engage more with video assignment because its more convenience for themcompare to writing traditional papers. Other than that, video recorded convey the visual, styleand delivery where it can help the students to produce interesting outputs. Lastly, it is recommended that video assignment is used extensively inside and outside the classroomwhere it adequately to expose the students with comprehensive and innovative learning tool.